2021
DOI: 10.23960/jhptt.221158-165
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF HOST-LARVAL DIET ON THE HOST ACCEPTANCE AND HOST SUITABILITY OF THE EGG PARASITOID Telenomus remus NIXON (Hymenoptera: Scelionidae) ON Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae)

Abstract: Effect of host-larval diet on the host acceptance and host suitability of the egg parasitoid Telenomus remus Nixon (Hymenoptera: Scelionidae) on Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae). The life history of parasitoids is an important factor that can determine their ability to attack a host. The type of food consumed by the host can affect the ability of parasitoids such as host searching behavior, host suitability and host acceptance. In this research, we evaluate the effect of the S. frugip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Sari et al [33] reported the potential of T. remus as a biological agent of S. frugiperda in Indonesia, with a parasitism rate of 69.40%. This value is comparable to other egg parasitoids such as T. chilotraeae [61]. The parasitism rate of T. remus may be higher in a situation with many potential hosts.…”
Section: Discussionsupporting
confidence: 74%
“…Sari et al [33] reported the potential of T. remus as a biological agent of S. frugiperda in Indonesia, with a parasitism rate of 69.40%. This value is comparable to other egg parasitoids such as T. chilotraeae [61]. The parasitism rate of T. remus may be higher in a situation with many potential hosts.…”
Section: Discussionsupporting
confidence: 74%
“…Sari et al [32] reported the potential of T. remus as a biological agent of S. frugiperda in Indonesia, with a parasitism rate of 69.40%. This value is comparable to other egg parasitoids such as T. chilotraeae [63]. The parasitism rate of T. remus may be higher in a situation with many potential hosts.…”
Section: Discussionsupporting
confidence: 74%
“…As previously documented, T. remus appears to have a similar parasitism level in eggs generated from adults fed either a natural or artificial diet when in the larval stage. However, the parasitization rate of T. remus in eggs derived from adults fed with an artificial diet during its larval stage was much lower than that reared with a natural diet [32] due to differences in the nutrients contained in the host's egg. In addition to the host condition, differences in the parasitization rate may also occur due to encapsulation [33], inhibiting the development of the parasitoid so that it fails to complete the life cycle.…”
Section: Discussionmentioning
confidence: 93%